Analisis Tupoksi Antara Konselor Adiksi dan Pekerja Sosial - Raudhatul Jannah; Meysa Malika; Ulina Tassia br Hutagaol; Gilberto Ronaldi (Pusat Riset dan Inovasi Nasional, 2024)
This analysis aims to determine the similarities and differences between the main tasks and functions of addiction counselors and social workers (Tupoksi) in the context of social services. Data were collected using qualitative descriptive methods and through in-depth interviews with experienced practitioners in both fields. Outcomes of analysis include individual and group counseling and client advocacy. However, differences were also observed in the intervention approach and primary focus. Addiction counselors tend to focus on rehabilitation and addiction-related treatment, while social workers often focus on the social and environmental recovery of their clients. This research provides insight into how these two professions can complement and collaborate in efforts to improve the well-being of individuals affected by addiction and other social issues.